GALERI SENI RUPA KIWARI DI SURAKARTA - Aryanto, Radityo; Nugroho, Rachmadi; Muqoffa, Mohamad (Universitas Sebelas Maret Surakarta, 2015)
Designing a Contemporary Art Gallery is considered by the rapid development of the art world, and contemporary art is part of the development which has great potential and practice in Surakarta, but the lack of facilities such as a gallery to display contemporary art. The purpose to be achieved is to design a gallery which is able to accommodate contemporary art and its development, to increase the appreciation of contemporary art, the quality of the artists, and the produced works of art. The method to be used is a method of architectural design. The main issues to be solved are: to choose and design the site as required location, the land use of Surakarta, and to be able to support the activities of contemporary art; to design spaces with the display systems which can answer the need of various contemporary art such as painting, printmaking, sculpture, video art, installation art, and environmental art. The result to be obtained is an art gallery which be able to display contemporary art in various forms and presentation, with the design of the building which is also contemporary, so that it can represents the works of contemporary art itself. Keywords: Gallery, Art, Contemporary, Display Rooms, Display, Surakarta